QTc interval prolongation and risk of atrial fibrillation recurrence: a meta-analysis and observational cohort study - Ding, Qiuju; Wang, Zhigang; Lu, Lichong; Song, Zhizhao; Ge, Min; Zhou, Qing (Frontiers in Cardiovascular Medicine, 2024)
IntroductionCorrected QT interval (QTc) is a ventricular repolarization marker on electrocardiography. Previous studies evaluated its value in predicting atrial fibrillation (AF) occurrence. However, its predictive efficacy for AF recurrence remains controversial.MethodsWe searched PubMed and Google databases for studies before January 2024 evaluating the association between QTc interval and AF incidence. A meta-analysis of the eligible datasets was conducted using Bazett's formula, with subgroup analysis to explore the heterogeneity. Additionally, thirty-eight patients with AF who underwent radiofrequency catheter ablation were enrolled and followed-up for 3–36 months. Univariate and multivariate Cox models were used to calculate the hazard ratios (HRs) and determine the relationship between clinical factors and AF recurrence. Kaplan-Meier survival analysis and ROC curve were conducted to assess the impact and predictive efficacy of individual factors.ResultsEleven datasets from nine eligible studies were enrolled and meta-analysed. We found that patients with prolonged QTc interval was associated with a significantly higher AF incidence risk, and the risk increased with every 10-ms prolongation. However, this association was not significant in the AF recurrence subgroup. In our prospective cohort, the preoperative body mass index, QTc, left atrial diameter (LAD), and uric acid levels influenced AF recurrence. Multivariate Cox regression analysis identified LAD as an independent factor affecting AF recurrence in patients with a high predictive efficiency. Kaplan-Meier survival analysis showed that increased LAD (>4.5 cm) was associated with postoperative AF recurrence.DiscussionTherefore, LAD has better predictive power and can be an indicator for predicting postoperative AF recurrence.